Systematic review of current research on vaccination of congenital heart disease children in China - LIU Na; WANG Huaqing; LUAN Lin; XU Juan; ZHENG Benfeng; HU Ran (Shanghai yufang yixue, 2024)
ObjectiveCongenital heart disease （CHD） is a common birth defect in children， with its incidence increasing annually. Because of their special health status， the vaccination situation for children with CHD has become a focal point of attention. This paper systematically reviews the current status of vaccination among children with CHD in China to identify existing issues in vaccination efforts for children with CHD， provide guidance for increasing vaccination rates among children with CHD， reduce the incidence of vaccine-preventable diseases， and provide ideas for subsequent research.MethodsLiterature on the vaccination of children with CHD in China was searched in both Chinese and English databases， including CNKI， Wanfang Data Knowledge Service Platform， VIP， Chinese Biomedical and Web of Science， PubMed， EmBase， and the Cochrane Library. Relevant literature was identified based on inclusion and exclusion criteria， and data extraction was carried out to summarize the research results.ResultsA total of 15 studies were included. Three articles focusing on expert consensus （guideline recommendations） for vaccination of children with CHD in China all agreed that vaccination is both feasible and necessary for children with CHD. Systematic analysis found that the overall timely vaccination rate for children with CHD was between 34% and 50%， with a notable delay in vaccination. However， after professional outpatient assessment， the vast majority of children with CHD were advised to be vaccinated according to the national recommended schedule， with only about 2% of them being advised to delay vaccination. The proportion of children with CHD who reported suspected adverse events following immunization （AEFI） was low and not significantly different from that of healthy/control children.ConclusionThe safety of vaccinations for children with CHD in China is relatively high， but the total timely vaccination rate is currently low. In order to improve the coverage and timeliness of vaccination in children with CHD， it is recommended that relevant departments provide vaccination policy support. There is a lack of research on the effectiveness of vaccination in children with CHD， so further studies are urgently needed to further improve the vaccination strategy for children with CHD in China.